Age-Related Macular Degeneration Revisited: From Pathology and Cellular Stress to Potential Therapies - Hadziahmetovic, Majda; Malek, Goldis (Frontiers in Cell and Developmental Biology, 2021)
Age-related macular degeneration (AMD) is a neurodegenerative disease of the aging retina, in which patients experience severe vision loss. Therapies available to patients are limited and are only effective in a sub-population of patients. Future comprehensive clinical care depends on identifying new therapeutic targets and adopting a multi-therapeutic approach. With this goal in mind, this review examines the fundamental concepts underlying the development and progression of AMD and re-evaluates the pathogenic pathways associated with the disease, focusing on the impact of injury at the cellular level, with the understanding that critical assessment of the literature may help pave the way to identifying disease-relevant targets. During this process, we elaborate on responses of AMD vulnerable cells, including photoreceptors, retinal pigment epithelial cells, microglia, and choroidal endothelial cells, based on in vitro and in vivo studies, to select stressful agents, and discuss current therapeutic developments in the field, targeting different aspects of AMD pathobiology.